Therapeutic effect of ofatumumab in patients with myasthenia gravis: immunoregulation of follicular T helper cells and T helper type 17 cells - Li, Shasha; Zhang, Zhaoxu; Liu, Zunjing (Frontiers in Neurology, 2023)
This study aimed to study the therapeutic effects of ofatumumab in patients with myasthenia gravis (MG) in addition to the immunomodulatory effects on peripheral follicular T helper (Tfh) cells and T helper type 17 (Th17) cells. Thirty-one patients with anti-acetylcholine receptor (AChR) antibody-positive MG were included in this study. At weeks 0, 1, 2, and 4, an initial dose of 20 mg of ofatumumab was injected subcutaneously, with a 2-month follow-up after completion of this first cycle. At baseline, 1 month, and 3 months, we assessed the Quantitative MG (QMG), 15-item MG-Quality of Life (MG-QOL15), and MG-Activities of Daily Living (MG-ADL) scales and measured the frequencies of Tfh cells, Th17 cells, and B cells and the levels of anti-AChR antibody, IL-6, IL-21, and IL-17 in the peripheral blood. At 1 month and 3 months, the QMG, MG-QOL15, and MG-ADL scores were all significantly reduced. At 3 months, doses of prednisone were reduced by an average of 37%. Decreased frequencies of Tfh cells and Th17 cells, depletion of B cells, and reduced levels of IL-6, IL-21, and IL-17 were all observed at 1 month or 3 months. Therefore, the therapeutic effect of ofatumumab could be detected after one cycle of treatment, which was maintained for 2 months. The immunomodulatory effect of ofatumumab during the observation period may involve depletion of B cells, reduction of Tfh cells and Th17 cells frequencies, and reduced levels of IL-6, IL-21, and IL-17. The findings provide novel data for the potential application of ofatumumab in MG.